New and renewable sources of energy - Essam (Dublin, 1983)
For almost a decade, the world has been stranded at an energy crossroads. The increases in oil prices since 1973 have had several far-reaching consequences. The shocks to the world economy caused by these increases have set in motion complex reactions, counter-reactions and adjustments that are still unfolding and are not yet fully understood.
Keywords: Energy